The Application of Contract Law Principles in Domestic Contracts - Asril Amirul, Zakariah; Zuhairah Ariff, Abd Ghadas; Farhanin, Abdullah Asuhaimi (Universiti Putra Malaysia, 2015)
A domestic contract refers to an agreement between persons having a family relationship. Despite the general rule of contract, parties in social, domestic and family agreements may not have the intention to create legal relations, but domestic contracts are legally binding. In the context of family law, domestic contracts normally involve marriage contracts and separation agreements that include, among others, the pre-nuptial agreement, settlement agreement, division of matrimonial property agreement and custody of children agreement. Despite the common nature and structure of the domestic contract as a typical agreement, there are concerns from family law practitioners that domestic contracts should be interpreted differently from the commercial or other types of contract and judges should have special or additional factors of consideration in giving effect to these contracts. In Malaysia, there is a proposal for the formation of a Family Court to improve procedures and provide better service to families. The main objective of the Family Court would be to empower the parties to resolve their disputes by mutual consent and in a manner that best serves the needs of the children involved. With the proposal for the establishment of a family court, it is very important for the court to determine the approaches that shall be applied by the said family court in domestic contracts in comparison to judicial approaches in commercial contracts. This paper examines approaches of the courts in dealing with family law contracts and compares them with the judicial approaches in domestic agreements between family members under general contract law. The research methodology adopted in this paper is the statutory and doctrinal analysis.